Quizizz-Assisted Interactive Powerpoint Media on Human Respiratory Organ Material - Ni Putu Dita Sri Cahyani; Ni Nyoman Ganing (Universitas Pendidikan Ganesha, 2022)
Student limitations related to cellphone devices make it difficult for students to follow the online learning process. The variety of learning media makes some students less interested in learning, and students lack understanding of the material being taught. This research is development research. This study aims to determine the design and test the validity of interactive Powerpoint media. This study used the ADDIE development model type. The types of data collected in this study are quantitative data and qualitative data. The subjects in this study included three experts and three students in individual trials, and nine students in small group trials. The data collection method uses the questionnaire method. The results of this study include (1) the design of this interactive Powerpoint media following the ADDIE model used with five stages of development. (2) Interactive Powerpoint media is declared feasible based on: (a) the results of expert reviews of learning content with excellent qualifications (90%), (b) the results of learning design reviews with excellent qualifications (90%), (c) the results of reviews of learning media with qualifications (90%), (d) the results of individual trials with excellent qualifications (96.66%), (e) the results of small group trials with excellent qualifications (95%). Based on the trial results, it can be concluded that this Quizizz-assisted interactive Powerpoint media is suitable for use in the science learning process of grade V elementary school.